Children's Physical Proximity to Interparental Conflict: Resilient Process and Retrospective Perceptions of Parent–Child Relationships - Bouteyre, Evelyne (Violence against women, 2024)
This retrospective study sought to determine (a) whether physical proximity to interparental conflict in childhood moderates the link between frequency of exposure to interparental conflict and subsequent levels of resilience in adulthood and (b) whether retrospective perceptions of parent–child relations and insecurity mediate the link between interparental conflict and resilient development. A total of 963 French students aged 18–25 years were assessed. Our study showed that the children's physical proximity to interparental conflict is a major long-term risk factor for their subsequent development and their retrospective perceptions of parent–child relations.